2015
DOI: 10.1063/1.4939198
|View full text |Cite
|
Sign up to set email alerts
|

A detailed analysis of the energy levels configuration existing in the band gap of supersaturated silicon with titanium for photovoltaic applications

Abstract: The energy levels created in supersaturated n-type silicon substrates with titanium implantation in the attempt to create an intermediate band in their band-gap are studied in detail. Two titanium ion implantation doses (10 13 cm -2 and 10 14 cm -2 ) are studied in this work by conductance transient technique and admittance spectroscopy. Conductance transients have been measured at temperatures of around 100 K. The particular shape of these transients is due to the formation of energy barriers in the conductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Despite the fact that from a theoretical point of view, the principle of operation of IBSC-type cells has been comprehensively described in [18], the problem of practical implementation of this concept in the form of a semiconductor material with an intermediate energy bandwidth, ensuring effective conversion of solar energy into electricity, still remains valid. Therefore, the mechanism of the formation of intermediate bands in semiconductors, as well as its utilitarian aspects, is the subject of many research papers, including a few selected current research directions based on the use of ion implantation [19][20][21][22][23][24][25]. One of them is an approach that includes the use of ion implantation to introduce dopants of very high concentration into the semiconductor substrate [25] or subjecting the silicon layer to implantation with metal ions of very high doses [20,23].…”
Section: Current Research Directions Using Ion Implantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that from a theoretical point of view, the principle of operation of IBSC-type cells has been comprehensively described in [18], the problem of practical implementation of this concept in the form of a semiconductor material with an intermediate energy bandwidth, ensuring effective conversion of solar energy into electricity, still remains valid. Therefore, the mechanism of the formation of intermediate bands in semiconductors, as well as its utilitarian aspects, is the subject of many research papers, including a few selected current research directions based on the use of ion implantation [19][20][21][22][23][24][25]. One of them is an approach that includes the use of ion implantation to introduce dopants of very high concentration into the semiconductor substrate [25] or subjecting the silicon layer to implantation with metal ions of very high doses [20,23].…”
Section: Current Research Directions Using Ion Implantationmentioning
confidence: 99%
“…Therefore, the mechanism of the formation of intermediate bands in semiconductors, as well as its utilitarian aspects, is the subject of many research papers, including a few selected current research directions based on the use of ion implantation [19][20][21][22][23][24][25]. One of them is an approach that includes the use of ion implantation to introduce dopants of very high concentration into the semiconductor substrate [25] or subjecting the silicon layer to implantation with metal ions of very high doses [20,23].…”
Section: Current Research Directions Using Ion Implantationmentioning
confidence: 99%
“…They are characterized by an intermediate energy band in the silicon band structure (although the idea of IBSC cells is not limited to silicon as the base material). Many studies have shown [28,29], that the implantation of a high resistivity silicon substrate with titanium ions in selected cases contributes to a significant increase in the absorption of photons whose energy is below the band gap width. The titanium ion implantation of the silicon substrate is aimed at the implementation of theoretical assumptions regarding the construction and structure of IBSC intermediate band photovoltaic cells, according to which the efficiency limit of such a cell is 63.2% [27], which is much higher than the limit of 47.1% [16] for conventional research solar cells with a single energy gap (Multijunction (4-junction or more, Concentrator)) [30].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this may be be possible for other elements such as chalcogens or transition metals. As a result, on the basis of experimental research conducted for titanium-implanted silicon, a detailed model of intermediate energy levels configuration was proposed [15]. The developed model theoretically explains the phenomena of energy level splitting, band gap narrowing and suppressing carrier recombination as a physical consequence of high impurities concentration.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is reasonable to investigate if it is possible to induce a shift in the value of E g using appropriately configured ion implantation and whether such operation will influence the performance of PV cells. Since the ion implantation and post-implantation treatment are the processes that require predetermining of a number of correlated variables, the aspect of consideration was a matter of many experimental and theoretical studies [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%